An integrated approach based on Life Cycle Assessment and Thermoeconomics: Application to a water-cooled chiller for an air conditioning plant. (1st October 2018) - Catrini, P.; Cellura, M.; Guarino, F.; Panno, D.; Piacentino, A.
Abstract: A large number of methods for energy systems analysis were developed in the last decades, aimed at acquiring an in-depth understanding of plant performances and enabling analysts to identify optimal design and operating conditions. In this work an integrated approach based on Life Cycle Assessment and Thermoeconomics is proposed as a method for assessing the exergo-environmental profile of energy systems. The procedure combines the capabilities of these two techniques, to account simultaneously for aspects related to thermodynamics of energy conversion processes and to the overall impacts along the plant life cycle related to other phases, i.e. from raw material extraction to the disposal of facilities. The capabilities of the method are illustrated by applying it to a water-cooled vapor compression chiller. After developing an accurate analysis of plant design and bill of materials of the chiller, the exergo-environmental profile was obtained. Then, the method was used as a decision support tool by considering a number of scenarios concerning possible design alternatives, context conditions and levels of maintenance. Results showed that the exergo-environmental performance of the chiller is highly sensitive to the electricity generation mix, which influences the trade-offs between the energo-environmental impacts related with plant operation and construction. Highlights: An approach combining Thermoeconomics and Life Cycle Assessment is proposed. Sensitivity to design, context condition and maintenance is studied for a chiller. The approach detects trade-off between opposing effects on environmental impacts. An oversized condenser achieves lowest exergy consumption but highest impacts. In renewables-based grid mix, the undersized evaporator achieves lowest impacts.